Extreme Value Analysis of Ocean Currents in the Mexican Caribbean Based on HYCOM Numerical Model Data - Ring, Michael; Rodríguez-Ocampo, Paola Elizabeth; Silva, Rodolfo; Mendoza, Edgar (Frontiers in Marine Science, 2022)
In designing offshore structures and ocean current turbines, comprehensive knowledge of extreme values is required. However, data on the return levels of ocean currents are rarely available. This is the case for the Mexican Caribbean, where a vast potential of energy has recently been detected in the ocean currents. This paper compares long-term numerical data from the Hybrid Coordinate Ocean Model for a depth of 50m and short-term empirical data for a depth of 49m in the Mexican Caribbean. Based on the numerical data, an extreme value analysis was conducted using the peaks over threshold method and fitting a generalized Pareto distribution through the data. The method relies on filtering peaks with a moving time window and an automated threshold selection, based on a reparameterized scale parameter of the generalized Pareto distribution. The numerical model is shown to overestimate the empirical data (i.e., 25% on average), leading to conservative results for this type of study. The method showed consistent results over the domain, with some anomalies at the boundaries of the underlying numerical model. The methodology is seen to be suitable for estimating the return levels based on ocean currents from the numerical model, although, more research is necessary to reduce the error of the numerical model and decrease the implicit safety factor of the results.